Arctic Societies, Cultures, and Peoples in a Changing Cryosphere - Grete K. Hovelsrud; Birger Poppel; Bob van Oort; James D. Reist (AMBIO, 2011)
Changes in sea ice, snow cover, lake and river ice, and permafrost will affect economy, infrastructure, health, and indigenous and non-indigenous livelihoods, culture, and identity. Local residents are resilient and highly adaptive, but the rate and magnitude of change challenges the current adaptive capacity. Cryospheric changes create both challenges and opportunities, and occur along local, regional, and international dimensions. Such changes will provide better access to the Arctic and its resources thereby increasing human activities such as shipping and tourism. Cryospheric changes pose a number of challenges for international governance, human rights, safety, and search and rescue efforts. In addition to the direct effects of a changing cryosphere, human society is affected by indirect factors, including industrial developments, globalization, and societal changes, which contribute to shaping vulnerability and adaptation options. Combined with non-cryospheric drivers of change, this will result in multifaceted and cascading effects within and beyond the Arctic.